1991
DOI: 10.1152/jappl.1991.71.4.1185
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen radical mechanisms of brain injury following ischemia and reperfusion

Abstract: This review addresses current understanding of oxygen radical mechanisms as they relate to the brain during ischemia and reperfusion. The mechanism for radical production remains speculative in large part because of the difficulty of measuring radical species in vivo. Breakdown of lipid membranes during ischemia leads to accumulation of free fatty acids. Decreased energy stores during ischemia result in the accumulation of adenine nucleotides. During reperfusion, metabolism of free fatty acids via the cyclooxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
256
0
5

Year Published

1995
1995
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 603 publications
(266 citation statements)
references
References 130 publications
(84 reference statements)
5
256
0
5
Order By: Relevance
“…This is in contrast to the situation in ischemic brain injury, in which lipid peroxidation is thought to play a more central role in the neuron death (Traystman et al 1991;Chan 1996;Liu et al 1998). However, it is quite plausible that the peroxidative damage could impair functional recovery in surviving neurons.…”
Section: Glutamate Neurotoxicitymentioning
confidence: 83%
“…This is in contrast to the situation in ischemic brain injury, in which lipid peroxidation is thought to play a more central role in the neuron death (Traystman et al 1991;Chan 1996;Liu et al 1998). However, it is quite plausible that the peroxidative damage could impair functional recovery in surviving neurons.…”
Section: Glutamate Neurotoxicitymentioning
confidence: 83%
“…Indirect strategies to study the role of ROS for ischemic damage have used compounds that inter act with ROS production (particularly ROS scaven gers; for overview see Traystman et al , 1991), and more recently transgenic approaches were used [i. e. , Cu-Zn-SOD overexpressing mice (Kinouchi et al , 1991;Halliwell et al , 1992)]. With very few exceptions, these studies have shown in a number of different ischemia models and species that exper imentally induced increases in the capacity of the brain to cope with oxidative stress are neuroprotec tive.…”
Section: Short Periods Of Hypoxia (Inhalation Of 100% N2)mentioning
confidence: 99%
“…There is evidence that free radical production is an important mechanism of brain injury after exposure to ischaemia and reperfusion (Traystman et al, 1991). While it is not possible to make direct measurements of antioxidant activity and oxidant damage in this target tissue, concentrations of antioxidants and products of oxidative damage in plasma have proved informative in other studies of stroke (Cherubini et al, 2000;Leinonen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…There is strong indirect evidence that free radical production is an important mechanism of brain injury after exposure to ischaemia and reperfusion (Traystman et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation